1994
DOI: 10.1103/physrevlett.73.1841
|View full text |Cite
|
Sign up to set email alerts
|

Critical Buckling for the Disappearance of Superconductivity in Rare-Earth-DopedLa2xSrxCu

Abstract: Analysis of the structural, transport, and superconducting properties of Nd-doped La2 "Sr Cu04 reveals a critical tilt angle of the Cu06 octahedra for the disappearance of superconductivity in the low temperature tetragonal phase. Our results indicate a strong inAuence of the tilt of the Cu06 octahedra on the electronic properties, suggesting the importance of spin-orbit coupling for the destruction of superconductivity and for the stabilization of a magnetic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(196 citation statements)
references
References 24 publications
11
185
0
Order By: Relevance
“…3(a) we show, for all x, the temperature dependence of the orthorhombic strain T HT . 30 Both quantities show a monotonic decrease with increasing x, as shown in the inset to Fig. 3(a) and in Fig.…”
Section: A Crystal Structurementioning
confidence: 71%
See 3 more Smart Citations
“…3(a) we show, for all x, the temperature dependence of the orthorhombic strain T HT . 30 Both quantities show a monotonic decrease with increasing x, as shown in the inset to Fig. 3(a) and in Fig.…”
Section: A Crystal Structurementioning
confidence: 71%
“…For La 2−x−y Nd y Sr x CuO 4 a critical tilt angle of 3.6 • has been identified to mark a phase boundary between SC and non-SC in the LTT phase. 30 This boundary is not very sharp and there are no reports yet on how deep charge stripe order persists into the SC LTT region with Φ < 3.6 • . The existence of such a critical angle is reasonable, since the symmetry breaking potential of the LTT phase should scale with Φ.…”
Section: Variation Of Parameters With Nominal Ba Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be related to the fact that in this material the direction of the collective octahedral tilts which exist is [11OJ (the so-called LTT-phase) rather than [loo] (the LTO phase) as in all the well superconducting variants [1,3]. It has been suggested that in the LTT phase, a critical buckling angle for the tilts destroys superconductivity [4], possibly-due to spin-lattice coup may also be a relationship of the tilt direction to the mobility of charge stripes which have been seen in related 214 materials [6].…”
Section: Introductionmentioning
confidence: 99%